The Gig Economy in Times of COVID-19: Designing for Gig Workers’ Needs - Vega, Juan Carlos Alvarez de la; Cecchinato, Marta E.; Rooksby, John (2020)
ABSTRACT Worldwide, the COVID-19 pandemic has disproportionately affected gig economy workers due to the contingent and precarious nature of their work. Many gig economy workers have had to adapt quickly to new forms of working, and even learn new skills, to sustain their livelihood. At the same time, gig economy companies have prioritised profit and customers’ needs over workers’ safety. In this position paper, we draw insights from recent academic literature, policy papers, and media reports from across the globe to explore broad implications the pandemic has had on gig economy workers. We then discuss how gig economy platforms might be re-designed to support better working conditions and foster workers’ development. CCS Concepts • Human-centered computing → Computer supported cooperative work. Keywords future of work, gig economy, worker-centred design, COVID-19 ABOUT THE AUTHOR/S Juan Carlos Alvarez de la Vega Northumbria University carlos.alvarez@northumbria.ac.uk I am a doctoral researcher at Northumbria University Social Computing Lab, working under the supervision of Dr Marta Cecchinato and Dr John Rooksby. My research focuses on gig economy freelancing platforms and worker-centred design approaches. Using qualitative and participatory methods, I explore how freelancing platforms impact their users' wellbeing. My professional experience and background are in design, community engagements and social innovation. Website: https://carlosalvarez.org Marta E. Cecchinato Northumbria University marta.cecchinato@northumbria.ac.uk John Rooksby Northumbria University john.rooksby@northumbria.ac.uk New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).